Three new patients with Steel syndrome and a Puerto Rican specific COL27A1 mutation. Issue 4 (5th January 2020) - Amlie‐Wolf, Louise; Moyer‐Harasink, Sue; Carr, Ann‐Marie; Giampietro, Philip; Schneider, Adele; Simon, Mitchell
Abstract: Steel syndrome was initially described by H. H. Steel in 1993 in Puerto Rico, at which time he described the clinical findings required for diagnosis. The responsible gene, COL27A1, was identified in 2015 (Gonzaga‐Jauregui et al., European Journal of Human Genetics, 2015;23:342–346). Eleven patients have previously been described with Steel syndrome and homozygous COL27A1 mutations, with eight having an apparent founder mutation, p.Gly697Arg. We describe three more patients identified at Einstein Medical Center Philadelphia and St. Christopher's Hospital for Children (Philadelphia, PA) diagnosed with Steel syndrome. All three are of Puerto Rican ancestry with the previously described founder mutation and had either hip dislocations or hip dysplasia. Radial head dislocation was only identified in one patient while short stature and scoliosis were noted in two of these patients. There are now 51 patients in the literature with Steel syndrome, including the 3 patients in this article, and 14 patients with a genetically confirmed Steel syndrome diagnosis.